Pengaruh kebijakan sosial dan kinerja lingkungan terhadap kinerja keuangan perusahaan manufaktur go public di Bursa Efek Indonesia - Joko Setyono (Journal of Business & Banking)
This study attempts to analyze the impact of Corporate Social Responsibilty and Envi-ronmental Performance in PROPER (Program Penilaian Peringkat Kinerja Perusahaan dalam pengelolaan Lingkungan Hidup/Performance Appraisal Evaluation Program in Life Environment) on Financial Performance. It used 20 manufacturing companies taken from annual report 2010 - 2012 of the manufacturing companies listed on Indonesian Stock Exchange and they also participated in PROPER since 2010. The data were ana-lyzed using the statistical method of multiple linear regressions. The results indicated that Corporate Social Responsibility and Environmental Performance has a significant effect on Financial Performance. It also showed that Corporate Social Responsibility has no significant effect on Financial Performance, while the Environmental Performance has a significant effect on Financial Performance. The impact of the results suggest that investor should consider Environmental Performance when invest on manufacture com-panies on Indonesia.